Pengaruh Intervensi Edukasi terhadap Pemahaman Berolahraga Pada Masyarakat Indonesia Berusia 18 Sampai 64 Tahun - Melisa Sonia Foris; Vito Anggarino Damay; Dyah Novita Anggraini (Syntax Corporation Indonesia, 2022)
Education is a process to educate aimed to develop knowledge and potential. Based on SUSENAS – 2018, there are only 35,7% of our Indonesian that exercise regularly. This survey proved that there are only about one third people that actually exercise actively. With so many benefits and positive impacts that we could get by exercising, it is expected to see our society to have decent knowledge and understanding about physical exercise. Therefore, this study is aimed to find out how the educated intervention impact physical exercise knowledge of Indonesians with age range from 18 until 64 years old, therefore will achieve healthy society with great health quality that will further impact on our national life expectancy. This study was done by using the experimental method (one group pretest-posttest design) towards the 110 samples of Indonesians with age from 18 until 64 years old with purposive sampling and Wilcoxon analitic study. The participants participated in the webinar and completes questionnaires before and after the intervention to asses their level of knowledge about exercise. The findings revealed a difference in the mean level of knowledge among respondents before and after the webinar, with pre-test score of 79,18 and post-test score of 96,82 out of 100 as the total score. There were significant difference in the mean level of knowledge and results showed that the intervention education increased the knowledge of participant with P<0,001. In conclusion, intervention education is proven to increase participant’s knowledge about physical exercise in Indonesian with age range from 18 until 64 years old.